MUSIKGESCHICHTE IN BILDERN — OSTAFRIKA. Vol. No..10, Ethnomusicological Series of VEB DeutscherVerlag fur Musik, Leipzig, 1982. By Gerhard Kubik with the cooperation of Jim de Vere Allen, Margot Dias, Ashenafi Kebede, Artur Simon and John Wembah-Rashid, general editor Werner Bachmann, pp.250,170 photographs colour and BW, diagrams, music. DDR 48.00 Mark, Order No. 518 211 9. - Mayr, Rupert (International Library of African Music, 1983)
pages: 126-127
Keywords: African Music